Detection of Propionibacterium in Samples by Metagenomic Analysis that Collected from Patients Suffering Acne Vulgaris in Babylon Province (Medico Legal Update, 2021)
By the metagenomic analysis detected the microorganisms in acne disease. The Taxonomic assignment ofthe sequences determined classified them into diverse microorganisms. In present study the microorganismswere bacteria (95.29%), eukaryote (4.23%), viruses (0.29%), archaea (0.04%), other sequences(0.15%) andunclassified sequences (0.00)these results determined for PA1. similarly, the PA2 was contains bacteria(96.52%), eukaryote (3.15%), viruses (0.18%), archaea (0.05%), other sequences(0.08%) and unclassifiedsequences (0.00). The identified and taxonomic of the bacteria that apparent high presenting 95.29% and96.52% for each PA1and PA2 respectively. According this results taxonomic of bacteria to genus presentto detected the important genus was infection acne. The PA1 sample was similarity with PA2. The genusbacteria for (PA1 and PA2) were Corynebacterium (34.67%, 40.32%), Propionibacterium (32.23%, 24.04%),Staphylococcus (24.54%, 24.18%), Malassezia (1.13%, 0.86%), Bacillus (0.92%, 1.99%), Pseudomonas(0.54%, 1.17%), Escherichia (0.36%, 0.52%), Acinetobacter (0.33%, 0.58%), unclassified (0.32%, 0.20%),Stenotrophomonas (0.31%, 0.51%), Meiothermus (0.30%, 0.36%) and Enterococcus(0.17%, 0.45%)whereas the PA2 have 0.18% of Streptococcus but the PA1 not appearance Streptococcu.